Paths to Clean Water Under Rapid Changing Environment in China - Li, Yiping; Ni, Lixiao; Guo, Yong.; Zhao, Xu.; Dong, Yue.; Cheng, Yu. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book mainly provides the current status of water pollution faced by China under rapid changing environment and the actions that have been taken for prevention and treatment of water pollution. It points out that the water pollution situation is severe. Facing water pollution, China's experiences include several aspects on source control and pollution interception, internal nutrient removal of sediment, ecological restoration, and water transfer policy. There exists both the opportunity and challenge for the prevention and control of water pollution in China. The book contains numerous charts and diagrams which further illustrating China's paths to clean water.
Current situation of water pollution in China -- Challenges and opportunities to treat water pollution -- Facing water pollution under rapid changing environment: China's experiences -- Conclusion.
Keywords: Pollution; Water; Hydrology; Environmental monitoring; Freshwater ecology; Marine ecology; Pollution; Water; Environmental Monitoring; Freshwater and Marine Ecology